2007
DOI: 10.1350/pojo.2007.80.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Community Policing: Broken Windows, Community Building, and Satisfaction with the Police

Abstract: The concept of community policing dominates the law enforcement profession today. One would be hard pressed to find an advertisement for a police chief's position that does not require a thorough understanding of this method of policing. Like the Kansas City preventive patrol experiment and the Rand report on the criminal investigation process, the call for community policing has led to dramatic changes in the way that police carry out their responsibilities. In spite of its popularity, there have been a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…While some authors used the term incivility instead (LaGrange et al 1992), Skogan (1990) determined two types of disorder: physical disorder, which involves rubbish in public areas, buildings in disrepair, noise, vandalism, graffiti, broken street furniture, and abandoned cars; and social disorder, which is the existence of gangs, youths hanging out on street corners intimidating elderly people, prostitutes, beggars, drunks, and gambling and substance abuse (Lombardo and Lough, 2007). Gau et al (2014) placed great emphasis on fear associated with BWT.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While some authors used the term incivility instead (LaGrange et al 1992), Skogan (1990) determined two types of disorder: physical disorder, which involves rubbish in public areas, buildings in disrepair, noise, vandalism, graffiti, broken street furniture, and abandoned cars; and social disorder, which is the existence of gangs, youths hanging out on street corners intimidating elderly people, prostitutes, beggars, drunks, and gambling and substance abuse (Lombardo and Lough, 2007). Gau et al (2014) placed great emphasis on fear associated with BWT.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Broken Windows theory has been a driving force in community policing programmers, because of the belief that unattended behaviour leads to the breakdown of community controls, thus leading to crime. Wilson and Killing, therefore, have called the police to pay urgent and serious attention to disorder and order maintenance policing [5].…”
Section: Broken Windows Theorymentioning
confidence: 99%
“…Community building according to them is a process by which police strengthen the capacity and resolute of citizens to resist crime by building positive relationships with community residents. [6], in his book The Politics of Community Policing, argues that innovative police strategies such as educational, recreational and occupational opportunities for youths, can mobilize the informal mechanisms of social control embedded within the community life [5]. Social control generally refers to the capacity of a particular group/ community to regulate its members.…”
Section: Community Implant Hypothesismentioning
confidence: 99%
“…Controlling for neighborhood structural disadvantage, neighborhood fear of crime, social cohesion, and perceptions of government responsiveness, Renauer's results indicated that community policing efforts were not positively related to informal social control. 1 Instead, the strongest predictors of informal social control were perceptions of neighborhood social cohesion and government responsiveness to neighborhoods (see also, Gill et al, 2014;Lombardo & Lough, 2007).…”
Section: Building Informal Social Control and The Community Implant Hmentioning
confidence: 99%